2009
DOI: 10.1038/ng.508
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the ankyrin domain of TRPV4 cause congenital distal SMA, scapuloperoneal SMA and HMSN2C

Abstract: Spinal muscular atrophies (SMA, also known as hereditary motor neuropathies) and hereditary motor and sensory neuropathies (HMSN) are clinically and genetically heterogeneous disorders of the peripheral nervous system. Here we report that mutations in the TRPV4 gene cause congenital © 2009 Nature America, Inc. All rights reserved.Correspondence should be addressed to M.A.-G. (michaela.auergrumbach@medunigraz.at).. METHODS: Methods and any associated references are available in the online version of the paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
198
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(210 citation statements)
references
References 30 publications
9
198
0
3
Order By: Relevance
“…We then examined the binding of the R232C, R269H, R315W and R316H mutants, identified in CMT2C and other diseases [7][8][9]25 . All of these mutants, except for R232C, showed significantly decreased binding to PI(4,5)P 2 -containing liposomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then examined the binding of the R232C, R269H, R315W and R316H mutants, identified in CMT2C and other diseases [7][8][9]25 . All of these mutants, except for R232C, showed significantly decreased binding to PI(4,5)P 2 -containing liposomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role of the cytoplasmic retention of TRPV4 channels and decreased calcium channel activity of the mutant TRPV4 in the pathogenesis of axonal neuropathies as described by AuerGrumbach et al (7) remains unclear. In their study showing a "loss of function" mechanism, the mutant TRPV4 channels appeared to have defects in transportation to plasma membrane, leading to cytoplasmic retention and loss of channel activity.…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, these data suggest a "gain of function" mechanism for mutant TRPV4-mediated axonal neuropathies. However, using tagged constructs, AuerGrumbach et al (7) found that the TRPV4 mutants (R269H, R315W, and R316C) accumulated exclusively in the cytoplasm in HeLa cells. They did not find any differences in basal calcium levels between wild-type and mutant TRPV4-transfected cells.…”
mentioning
confidence: 99%
“…Mutations in the human TRPV4 gene have been identified as the direct cause of divergent hereditary diseases, including skeletal dysplasias, spinal muscular atrophy, and CharcotMarie-Tooth disease type 2C (36)(37)(38)(39)(40)(41). Although the exact role of TRPV4 in the etiology of these clinically diverse diseases is unknown, it appears that many disease-causing mutations lead to gain of TRPV4 function (41).…”
Section: Discussionmentioning
confidence: 99%